Life cycle assessment of a vanadium flow battery. (February 2020) - Gouveia, J.; Mendes, A.; Monteiro, R.; Mata, T.M.; Caetano, N.S.; Martins, A.A.
Abstract: Battery storage technologies have been showing great potential to address the vulnerability of renewable electricity generation systems. Among the various options, vanadium redox flow batteries are one of the most promising in the energy storage market. In this work, a life cycle assessment of a 5 kW vanadium redox flow battery is performed on a cradle-to-gate approach with focus on the vanadium electrolytes, since they determine the battery's storage capacity and can be readjusted and reused indefinitely. The functional unit is 1 kWh stored by the battery. The initial results show that the environmental hotspots reside mainly in the structural and material components of the battery, evidencing the need for alternative or recycled materials, preferably produced locally. Since the quantity of electrolytes determine the amount of storable electricity, an analysis was conducted on the variation of the impacts with the increase of storage capacity. An alternative scenario with reused electrolytes was also performed. Results show that with the increase of storage capacity, the contribution of the electrolytes to the impacts decrease significantly by stored kWh. In the reused electrolytes scenario, impacts were reduced mainly for the Acidification and Mineral, fossil and renewable resource depletion categories.